Transcatheter Aortic Valve Replacement Incidentalomas: A Multimodality Imaging Case of Giant Right Coronary Aneurysm - Jamal Janjua; Esosa G. Odigie-Okon; Premnauth Rabindranauth; Richard J. Wittchow; Aiman Riaz (Case Reports in Cardiology)
Giant coronary artery aneurysms (CAAs) are defined as having a diameter of greater than 2 cm. We report a case of an 82-year-old male with severe aortic stenosis incidentally diagnosed with giant right coronary artery aneurysm (gRCAA) while undergoing evaluation for transcather aortic valve replacement (TAVR). It was causing a mass effect on the right cardiac chambers but was otherwise asymptomatic. Our patient was successfully treated with surgical excision of aneurysm with concomitant coronary artery bypass grafting (CABG) and surgical aortic valve replacement (SAVR). The patient remained stable at discharge and on serial follow-ups for two years. In conclusion, due to the associated complication and increased risk of mortality with giant coronary aneurysms, we recommend surgical approach instead of medical management alone. We also call for evidence-based recommendations and guidelines for management of TAVR incidentalomas.